Clinicopathological and Prognostic Significance of the EML4-ALK Translocation and IGFR1, TTF1, Napsin A Expression in Patients with Lung Adenocarcinoma - Pınar BULUTAY; Nalan AKYÜREK; Leyla MEMIŞ (Federation of Turkish Pathology Societies, 2021)
Objective: Patients with lung adenocarcinoma who harbor ALK gene rearrangements can demonstrate significant clinical benefit with ALK tyrosine kinase inhibitors. Insulin-like growth factor receptor 1 (IGFR1) is a cellular membrane receptor that is overexpressed in many tumors. It plays an important role in cancer progression and is associated with increased postoperative recurrence and poorer disease-free survival. The aim of this study was to determine the EML4-ALK mutation and IGFR1 expression in lung adenocarcinoma and analyze their prognostic value. Material and Method: In this study, we analyzed the EML4-ALK mutation using the FISH and IHC techniques in 251 lung adenocarcinoma (203 primary resections, 48 metastasectomies) cases. Correlative analyses were performed between the EML4-ALK mutation, the IGFR1, TTF1, and NapsinA expression, and the clinicopathologic factors in lung adenocarcinomas. Results: The EML4-ALK mutation was observed in 3.8% of the cases and it was associated with the solid pattern, signet ring cell morphology, and larger tumor size. IGFR1 expression was identified in 49% of the cases and most of the ALK-mutated cases were also expressing the IGFR1 protein (66%). IGFR1 expression frequency was increased in metastasectomy specimens. Conclusion: A solid signet-ring cell pattern or mucinous cribriform pattern was present at least focally in all ALK-positive tumors, consistently with the literature. In addition, IGFR1 expression levels showed an increase in the EML4-ALK-mutated cases in our series, but the clinical significance of this finding should be supported by larger series and survival analysis. Our findings show that IGFR1 expression may be useful as a poor prognostic marker in patients with lung adenocarcinoma.